2009
DOI: 10.1364/ao.48.002086
|View full text |Cite
|
Sign up to set email alerts
|

Third-generation megahertz-rate pulse burst laser system

Abstract: The design and performance of a third-generation megahertz-rate pulse burst laser system is described. The third-generation system incorporates two distinct design changes that distinguish it from earlier-generation systems. The first is that pulse slicing is now achieved by using an economical acousto-optic modulator (AOM), and the second is the use of a variable pulse duration flashlamp driver that provides relatively uniform gain over a ~700 mus window. The use of an AOM for pulse slicing permits flexible o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…To overcome the challenges associated with conventional high-average-power continuously pulsed DPSS lasers, it is possible to employ burst-mode laser technology in which the pulse sequence can reach energies of 100's of mJ per individual pulse up to MHz rates, while maintaining low average power [8][9][10][11][12]. This technology has been demonstrated for high-speed measurements of temperature [13]; mixture fraction [14]; PLIF of OH [10,15], NO [12,16,17], CH [18][19][20], and CH 2 O [21,22]; and Raman line imaging of O 2 , N 2 , CH 4 , and H 2 [23], with measurements ranging from 1 kHz to 1 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the challenges associated with conventional high-average-power continuously pulsed DPSS lasers, it is possible to employ burst-mode laser technology in which the pulse sequence can reach energies of 100's of mJ per individual pulse up to MHz rates, while maintaining low average power [8][9][10][11][12]. This technology has been demonstrated for high-speed measurements of temperature [13]; mixture fraction [14]; PLIF of OH [10,15], NO [12,16,17], CH [18][19][20], and CH 2 O [21,22]; and Raman line imaging of O 2 , N 2 , CH 4 , and H 2 [23], with measurements ranging from 1 kHz to 1 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these techniques are somewhat prohibited by the low pulse energies of commercially available DPSS lasers. Similarly, many important combustion radicals such as CH, O, H, or NO cannot be imaged using PLIF because the UV laser energy obtained using commercial systems is too low.As an alternative to a continuous duty cycle, previous authors have demonstrated the ability to generate a limited number of higher energy pulses at high repetition rates (e.g., [4][5][6][7][8][9]). Perhaps the best-known examples of these types of laser systems are pulse-burst Nd:YAG systems that can produce a series of sequential pulses at repetition rates as high as 1 MHz [10] and pulse energies exceeding hundreds of millijoules at kilohertz rates (e.g., 11-17]).…”
mentioning
confidence: 99%
“…As an alternative to a continuous duty cycle, previous authors have demonstrated the ability to generate a limited number of higher energy pulses at high repetition rates (e.g., [4][5][6][7][8][9]). Perhaps the best-known examples of these types of laser systems are pulse-burst Nd:YAG systems that can produce a series of sequential pulses at repetition rates as high as 1 MHz [10] and pulse energies exceeding hundreds of millijoules at kilohertz rates (e.g., [11][12][13][14][15][16][17]).…”
mentioning
confidence: 99%
“…The temporal resolution was achieved by sampling with pulses of our Satsuma laser system (Amplitude Systèmes, Pessac, France) in delay steps of 100 ps, while the transmission at each point was determined as an average value. The curve was fitted using Equation (2). The 10%-90% rise time was determined to be 7.4 ns.…”
Section: Methodsmentioning
confidence: 99%
“…Among these are, for example, the detection of fast processes in combustion diagnostics with methods like particle image velocimetry (PIV), planar laser-induced fluorescence (PLIF) analysis, planar Rayleigh scattering or planar Doppler velocimetry (PDV) [1][2][3][4]. Furthermore, such pulse bursts may be applied in laser ablation [5,6] or in photoinjectors, which are used to create electron pulses in conventional particle accelerators [7].…”
Section: Introductionmentioning
confidence: 99%